Anthropometric aspects of body seated in school - Reis, P.; Moro, A. R.; Da Silva, J. [UNESP]; Paschoarelli, L. [UNESP]; Nunes Sobrinho, F.; Peres, L. (IOS Press, 2012)
This study aimed to assess the student-furniture interface from anthropometric parameters of the sitting posture. The sample was composed of 887 students from two public schools in the State of Parana - Brazil, which attended children from 7 to 17 years of age. The data collection used anthropometric measures of the sitting position, a questionnaire containing a human body diagram for indication of discomfort areas and photographic records to verify postural and ergonomic inadequacies in classroom. The following anthropometric variables were measured: popliteal height, sacro-popliteal length, hip width, lumbar support height, and elbow and thigh height. Percentiles 5 and 95 of anthropometric variables showed differences statistically significant, with variation coefficient greater than 30%. In relation to body discomfort, the highest occurrences were recorded for ankle, knees and shoulder joints as well as for spine and buttocks. It was concluded that children use school furniture that does not meet their anthropometric standards, which favored the adoption of incorrect postures and contributed to the emergence of musculoskeletal problems that can interfere with their educational process.
Keywords: Seating posture; Discomfort; School furniture